The Resting-State Electroencephalogram Microstate Correlations With Empathy and Their Moderating Effect on the Relationship Between Empathy and Disgust - Zhang, Meng; Li, Zhaoxian; Wang, Li; Yang, Shiyan; Zou, Feng; Wang, Yufeng; Wu, Xin; Luo, Yanyan (Frontiers in Human Neuroscience, 2021)
Abstract: Humans have a natural ability to understand the emotions and feelings of others, whether one actually witnesses another’s situation, perceives it from a photograph, reads about it in a fiction book, or merely imagines it. This is the phenomenon of empathy, which requires us to mentally represent external information to experience others’ emotions. Studies have shown that individuals with high empathy have high anterior insula and adjacent frontal operculum activation when they are aware of negative emotions in others. As a negative emotion, disgust processing involves insula coupling. What are the neurophysiological characteristics for regulating the levels of empathy and disgust? To answer this question, we collected EEG microstates (EEG-ms) of 196 college students at rest and used the Disgust Scale (DS) and Interpersonal Reactivity Index (IRI). The results showed that: (1) there was a significant positive correlation between empathy and disgust sensitivity (2) the empathy score and the intensity of transition possibility between EEG-ms C and D were significantly positively correlated (3) the connection strength between the transition possibility of EEG-ms C and D could adjust the relationship between the disgust sensitivity score and the empathy score. This study provides new neurophysiological characteristics for an understanding of the regulate relationship between empathy and disgust, and provides a new perspective on emotion and attention.